Antigone's Example: Early Modern Women's Political Writing in Times of Civil War from Christine de Pizan to Helen Maria Williams. - Green, Karen (Sixteenth Century Journal)
The article critiques a book that explores the theme of women writers during periods of civil war, beginning with Sophocles's *Antigone* and concluding with Helen Maria Williams's *Letters Written in France*. The author argues that while the book attempts to connect civil conflict with women's political writing, it suffers from a lack of coherence due to its broad scope and insufficient exploration of the political doctrines of the women discussed. Key figures such as Christine de Pizan, Anne Dowriche, and Margaret Cavendish are mentioned, but their political contexts and contributions are often inadequately addressed, leading to a fragmented understanding of women's roles in political discourse during the examined periods. The article suggests that despite the extensive scholarship, the book ultimately fails to provide a comprehensive overview of the political ideas of women writers.